Разработка кандидатной субстанции рекомбинантного белка CRM197 - E. G. Bogomolova; O. A. Dobrovol'skaya; A. A. Mirovskaya; R. I. Al-Shehadat; E. A. Fedorova; I. V. Dukhovlinov; A. S. Simbirtsev (Эпидемиология и вакцинопрофилактика)
CRM197 is a non-toxic mutant of diphtheria toxin having a single amino acid substitution of a glycine for a glutamic acid in position 52. Being naturally nontoxic, CRM197 is a promising adjuvant and ideal carrier protein for conjugate vaccines. Typically, production of diphtheria toxic and non-toxic mutants are carried out in Corynebacterium diphtheria. Production of recombinant CRM197 in Escherichia coli is advantageous. It is simple, cheap and permits production of the target protein in a short time using a non-pathogenic microorganism. In this study the pharmacology grade substance of recombinant protein CRM197 was developed based on chemical properties of the protein. The substance of recombinant protein CRM197 is characterized by presence of 0.054 ng/mcg of CRM197 E. coli host cell protein, 1.26 pg/mcg of CRM197 E.coli Host Cell DNA and less than 0,078 EU endotoxins per 1 mg of recombinant protein CRM197.